ISO 9000: Evolution towards total quality (Publicaciones en Ciencias y Tecnología, 2020)
This article is intended to analyze the evolution of the quality management concept through the ISO 9000 series of standards. To this end, the versions of these standards are examined and compared with the quality management definitions proposed by different authors. The results of this research make it possible to conclude that the ISO 9000 series of standards has been changing its position with regard to quality management, moving from a product-centric model to one focused on market demands. There is a greater influence, in the most recent versions of the standard, of the principles and practices of Total Quality materialized especially in the eight principles and in the model of the process-based Quality Management System, defined in the version of the year 2000 and maintained and deepened in the versions of 2008 and 2015.
Keywords: quality management; ISO 9000; total quality; standards